A comparative analysis of tobacco and alcohol consumption patterns underlying hypertension prevalence across Indian women: evidence from National Family Health Survey-5 - Yadav, Shanvi; Siddiqui, Aamir (International Journal Of Community Medicine And Public Health, 2024)
The rise of hypertension among women poses a significant public health challenge in India, affecting 1 in 4 individuals. Multiple factors lead to this surge, including changing eating habits, emergence of substance consumption such as tobacco, alcohol, and both reflecting the evolving lifestyles. This study utilizing the national family health survey (NFHS)-5 data from DHS website with a total of 724,115 women from both rural and urban using statistical package for the social sciences (SPSS) version 23. Binomial logistic regression, was used to examine the association between hypertension and individual, household, and behavioral factors. Overall, 4.6% of women are affected by hypertension. The study also revealed that 6.2%, 1.9%, and 7.7% of women respectively, reported using tobacco, alcohol, and both substances simultaneously. Further analysis showed that those who used tobacco (4.9%) and alcohol (6.0%) had a higher prevalence of hypertension compared to non-users (4.6%). The highest occurrence of hypertension was observed among those who used both substances (5.1%). This aligns with the results of adjusted logistic regression, which confirmed that tobacco use (OR=1.073), alcohol use (OR=1.325), and dual-use (OR=1.129) were all significantly linked to a higher likelihood of developing hypertension. This study highlights the need for appropriate health services for screening and treatment and immediate action to reduce the uptake of these substances.